CHAUPIÑAMCA AND CASAYACO DANCING: PRELIMINARY STUDY OF ICONOGRAPHIC MANTLE FOUND BY MAX UHLE ON THE ISLAND SAN LORENZO - Hudtwalcker Morán, José Antonio (2011)
In 1907, Max Uhle performed excavations at the La Cruz Creek, located in the San Lorenzo Island. One of the most important objects discovered during that exploration was a mantle with a painting representing a parade of naked people. The painted mantle and other objects retrieved from the island by Uhle are kept at the Museo Nacional de Arqueología, Antropología e Historia del Perú. The iconographic study was based on a semiologic approach. As long as the characters, their attrbutes and their actions are properly identified, this approach leads to fine results on the meaning of the representations. Chronologically, the mantle pertains to the Late Horizon (1470-1532 dC.) and culturally is related to the Ichma style, from the Rimac and Lurín valleys. The Ichma style shares some features with northern styles such as Chancay, Chimú and Lambayeque. The mantle was compared to the data offered by the Manuscript of Huarochirí regarding the dance of Casayaco, a celebration in honor of the goddess Chaupiñamca. Although it cannot be ascertained with certainty that the mantle represents that dance, the iconographic analysis provided strong arguments in order to establish a relationship between the representation of the mantle and the rituals in honor of that divinity. Therefore, the design of the mantle may be an incitement to the fertility of the land and to the prosperity of the community.